A systematic review of the effect of thermal processing on the allergenicity of tree nuts. Issue 8 (29th July 2013) - Masthoff, L. J.; Hoff, R.; Verhoeckx, K. C. M.; van Os‐Medendorp, H.; Michelsen‐Huisman, A.; Baumert, J. L.; Pasmans, S. G.; Meijer, Y.; Knulst, A. C.
Abstract: Background: Allergenicity of foods can be influenced by processing. Tree nuts are an important source of nutrition and increasingly consumed; however, processing methods are quite variable and data are currently lacking on the effects of processing on allergenicity. Objective: To perform a systematic literature review on the effects of food processing on the allergenicity of tree nuts. Methods: A systematic literature search of PubMed and Embase databases was performed, with screening of references, related articles and citations. Studies were included if they assessed the allergenicity or immunogenicity of processed nuts. Results: The search resulted in 32 articles suitable for analysis. Clinical studies indicate that roasting reduces the allergenicity of hazelnut in individuals with a birch pollen allergy and reactivity to raw hazelnut. Thermal processing may reduce the allergenicity of the PR‐10 protein in hazelnut and almond in vitro . The majority of the in vitro studies investigating the allergenicity of nonspecific lipid transfer proteins (nsLTPs) and seed storage proteins in hazelnut, almond, cashew nut, Brazil nut, walnut, pecan nut and pistachio nut show heat stability towards different thermal processing methods. Conclusion: Thermal processing may reduce allergenicity of PR‐10 proteins in hazelnut and almond, in contrast to nsLTPs and seed storage proteins. This has important implications for source materials used for IgE testing and food challenges and diet advice.